Popular orange-fleshed sweetpotato products in Rwanda: Biscuits and doughnuts - Magnaghi, A.; Muzhingi, T.; Sindi, K.; Gerard, S. (International Potato Center, 2015)
Golden Power Biscuits and mandazi (fried doughnuts) have emerged as the top products made with freshly prepared orange-fleshed sweetpotato (OFSP) puree at Urwibutso Enterprises. This flyer shares the process and recipe or preparing these popular products.